THE INFLUENCE OF THE PjBL-HOTS LEARNING MODEL ON LEARNING OUTCOMES COGNITIVE AND METACOGNITIVE IN STUDENTS AT SMAN 5 CENTRAL MALUKU - Aska, Aska; Rumahlatu, Dominggus; Rehena, Johanis Fritzgal (Universitas Pattimura, 2022)
PjBL-HOTS is a learning that emphasizes contextual learning which is implemented through project activities in this project learning is carried out on a hots basis so that students can think more critically, creatively and actively in constructing learning and be able to solve problems in everyday life. This study aims to determine the effect of the PjBL-HOTS learning model on students' cognitive and metacognitive learning outcomes. This research was conducted at SMAN 5 Central Maluku on April 28 to May 28, 2021, which is located in Tulehu village. The method used is a quasi-experimental design. Based on the LSD further test, it shows that PjBLHOTS learning can affect students' cognitive learning outcomes as evidenced by the increase in cognitive and metacognitive learning outcomes with the average difference between the pretest and posttest cognitive results, which is -23.08571 and the average metacognitive value, which is 16.18081. learning that is done without a project. The results of this study indicate that the use of the PjBL-HOTS learning model can affect students' cognitive and metacognitive learning outcomes.